Human capital, digital transformation, and firm performance of startups in Vietnam - Ghi Tran Nha; Thu Nguyen Quang; Huan Ngo Quang; Trung Nguyen Tan (Zielona Góra: Faculty of Economics and Management Press)
Based on social capital theory, the study explained the digital transformation process of startups in Vietnam. The primary object of this study is to examine the relationship between human capital, digital transformation, and firm performance of startups in Vietnam. The study applied Partial Least Squares Structural Model (PLS-SEM) with a sample size of 230 managers.
Keywords: human capital; digital transformation; firm performance; kapitał ludzki; transformacja cyfrowa; wydajność firm